Investigating the pathways between swift trust and team creativity among nursing student teams in Taiwan: A moderated mediation model - Hsing-Yuan Liu (BMC, 2022)
Abstract Background Considerable theoretical and empirical work indicates that a multitude of factors are associated with team creativity in an organizational context. The complex relationships between the contributors, however, are not well understood in nursing education. This study was to take a process view investigating the pathways from swift trust to creativity via collaborative interactions and to explore whether task conflict would further change the strength of the indirect effect. Methods This study utilized a cross-sectional, quantitative, descriptive design. Taiwanese nursing students (final n = 629), who enrolled in capstone courses of small interdisciplinary groups collaborating with industrial design students on designing healthcare products, participated in the study. Data were collected from students during 2018 and 2020. Questionnaires assessed their perceptions about teams' swift trust (including cognition- and affect-based), collaborative interactions (including constructive controversy, helping behavior, and spontaneous communication), task conflict, and creativity. SPSS PROCESS macro was used to test the proposed moderated mediation model. Results Bivariate correlation analysis showed that greater team creativity was associated with increased cognition-based team swift trust and collaborative interactions. Results revealed that collaborative interactions serving as the underlying mechanisms mediating the effect of cognition- and affect-based swift trust on team creativity. Moreover, the indirect effect of collaborative interactions, specifically, spontaneous communication, on linking swift trust to team creativity varied as a function of task conflict. As task conflict decreased, the effect became stronger. Conclusion Findings suggest that nursing student teams' spontaneous communication serves as the underlying mechanism in linking the relationship between swift trust and team creativity and that lower task conflict plays a crucial role in enhancing the indirect effect. The proposed pathway could provide guidance for nursing educators to promote creativity outcomes by promoting swift trust and collaborative interactions as well as preventing task conflict for interdisciplinary nursing student teams.